The impact of ICT adoption in hotel industry / Nur Iman Syahrainn Masnawi and Nurshahira Zulaikha Zainudin - Masnawi, Nur Iman Syahrainn; Zainudin, Nurshahira Zulaikha (2019)
Technology nowadays is very crucial especially the usage of information and communication technology (ICT) in hotel industry because it is a part of the operation that helps the hotel to run effectively and efficiently. Hence, it is one part of the big investment for a hotel to create a personal engagement since ICT has been rapidly changed or being improvised from time to time. The importance of the study that had been conducted is to highlight the impact of ICT in various perspectives. However, in order to understanding the impact of ICT throughout the years, a narrative review of the key existing should have been undertaken. Therefore, this paper aims to identify and investigate the impact of ICT adoption towards the hotel industry which might also influence the hotel performance during service delivering process. This paper argues about the impact of ICT adoption in hotel industiy. The result shows the important impacts of ICT adoption toward hotel industry includes ICT design, ICT utilization, modem technology, benefits and its drawbacks. Overall of this study brings an argumentative contribution in summarizing ICT affect more on hotel performance. ICT design, ICT utilization, modem technology give impact of ICT adoption towards hotel industry.